Immunohistochemical localisation of Glutamate ammonia ligase (GLUL) in cerebrum in different clinical forms of canine rabies - P. Nikhithasree; C. Divya; M.L. Arya Nair; K. Krithiga; K.S. Prasanna; Lali F. Anand; John Bernet Johnson (Journal of Veterinary and Animal Sciences, 2023)
Rabies, one of the earliest known diseases reported in the history of mankind, is a fatal acute viral disease of the central nervous system. Despite numerous studies on etiology of rabies, its exact mechanism of neuropathogenesis remains unidentified. Glutamate ammonia ligase (GLUL) is a protein present in brain which play an important role in the pathogenesis of many neurological conditions. GLUL was identified to be over expressed in brain of human rabies. Cerebral cortex is the part of brain primarily responsible for coordination of movements and behaviour in animals and humans. Hence the work was designed to study the immunohistochemical localisation of GLUL in cerebrum in rabid carcasses in order to elucidate its role in the pathology of this deadly viral infection. The carcasses of 219 rabies suspected dogs that were brought to the Department of Veterinary Pathology, CVAS, Mannuthy, for necropsy between January 2021 and August 2022 formed the materials for the study. One hundred and thirty-three cases were found positive for rabies using the gold standard test for rabies - Direct Fluorescent Antibody Test (dFAT) which was further confirmed by polymerase chain reaction targeting N gene with amplicon size 533 bp. Among these 133 confirmed cases, 30 selected samples (frontal, occipital, temporal, parietal lobes of cerebrum) were further processed for histopathological and immunohistochemical (IHC) studies. The IHC signals of GLUL obtained were compared with the clinical form of rabies. Immunohistochemical staining revealed localisation of GLUL in glial cells with different staining intensity in encephalitic and paralytic form of rabies. The study concluded that the IHC signals for GLUL were stronger for furious form of rabies and weak for dumb form of the disease.